2022
DOI: 10.1186/s12885-022-09524-1
|View full text |Cite
|
Sign up to set email alerts
|

An immune-related lncRNA pairs signature to identify the prognosis and predict the immune landscape of laryngeal squamous cell carcinoma

Abstract: Background Laryngeal squamous cell carcinoma (LSCC) is the most common squamous cell carcinoma. Though significant effort has been focused on molecular pathogenesis, development, and recurrence of LSCC, little is known about its relationship with the immune-related long non-coding RNA (lncRNA) pairs. Methods After obtaining the transcriptome profiling data sets and the corresponding clinical characteristics of LSCC patients and normal samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…The previous prognostic signatures in other cancers showed better diagnostic performance, with an AUC value of more Frontiers in Molecular Biosciences frontiersin.org than 0.8 (Qian et al, 2022;Zhang et al, 2022). However, in the current study, the AUC value for OS at the 5 year periods was 0.657 in TCGA and 0.717 in GSE31210.…”
Section: Frontiers In Molecular Biosciencescontrasting
confidence: 74%
See 1 more Smart Citation
“…The previous prognostic signatures in other cancers showed better diagnostic performance, with an AUC value of more Frontiers in Molecular Biosciences frontiersin.org than 0.8 (Qian et al, 2022;Zhang et al, 2022). However, in the current study, the AUC value for OS at the 5 year periods was 0.657 in TCGA and 0.717 in GSE31210.…”
Section: Frontiers In Molecular Biosciencescontrasting
confidence: 74%
“…In the present study, the redox-related gene signature was first constructed in all the patients with NSCLC, and Kaplan–Meier survival curve showed that the high-risk group had a worse OS than the low-risk group, which was different from and cannot be replaced by the previously constructed signature using hypoxia-related gene ( Chen et al, 2022 ), pyroptosis-related gene ( Zhang and Yan, 2021 ; Li et al, 2022 ), autophagy-related gene ( Wu et al, 2021a ), and inflammatory response-related gene ( Zou et al, 2021 ) because it could be meaningful in exploring the value of the redox-related gene in initiation, progression, prognosis, and therapy of NSCLC. The previous prognostic signatures in other cancers showed better diagnostic performance, with an AUC value of more than 0.8 ( Qian et al, 2022 ; Zhang et al, 2022 ). However, in the current study, the AUC value for OS at the 5 year periods was 0.657 in TCGA and 0.717 in GSE31210.…”
Section: Discussionmentioning
confidence: 93%
“…AC002451 is one of the ferroptosisrelated lncRNAs related to poor prognosis of gastric adenocarcinoma (26). Some studies have shown that linc02154 may serve as a valuable biomarker to predict the prognosis and indicate the immune status in laryngeal squamous cell carcinoma and as a potential therapeutic target (27)(28)(29). Another study indicated that LINC02154 facilitates hepatocellular carcinoma proliferation and metastasis by enhancing SPC24 promoter activity and activating the PI3K-AKT signaling pathway (30).…”
Section: Discussionmentioning
confidence: 99%
“…An axis linking an lncRNA with a microRNA and the target gene was shown in bladder cancer progression and metastasis [ 48 , 49 ]. A similar approach has been used to study laryngeal squamous cell carcinoma [ 50 ].…”
Section: Discussionmentioning
confidence: 99%